In vitro inhibition of histamine release behavior of cetirizine intercalated into Zn/Al- and Mg/Al-layered double hydroxides - Al Ali, Samer Hasan Ahmad Hussein; Al-Qubaisi, Mothanna Sadiq Obaid; Hussein, Mohd Zobir; Ismail, Maznah; Zainal, Zulkarnain; Abdullah, Muhammad Nazrul Hakim (MDPI, 2012)
The intercalation of cetirizine into two types of layered double hydroxides, Zn/Al and Mg/Al, has been investigated by the ion exchange method to form CTZAN and CTMAN nanocomposites, respectively. The basal spacing of the nanocomposites were expanded to 31.9 Å for CTZAN and 31.2 Å for CTMAN, suggesting that cetirizine anion was intercalated into Layered double hydroxides (LDHs) and arranged in a tilted bilayer fashion. A Fourier transform infrared spectroscopy (FTIR) study supported the formation of both the nanocomposites, and the intercalated cetirizine is thermally more stable than its counterpart in free state. The loading of cetirizine in the nanocomposite was estimated to be about 57.2% for CTZAN and 60.7% CTMAN. The cetirizine release from the nanocomposites show sustained release manner and the release rate of cetirizine from CTZAN and CTMAN nanocomposites at pH 7.4 is remarkably lower than that at pH 4.8, presumably due to the different release mechanism. The inhibition of histamine release from RBL2H3 cells by the free cetirizine is higher than the intercalated cetirizine both in CTZAN and CTMAN nanocomposites. The viability in human Chang liver cells at 1000 μg/mL for CTZAN and CTMAN nanocomposites are 74.5 and 91.9%, respectively.